Developing Student Academic Ability Using Scaffolding Method In Cognitive Apprenticeship Model - Akhmad Ramli; Mihrab Afnanda; Roinah Roinah; Syafrida Damanik; Andika Isma (Mudir : Jurnal Manajemen Pendidikan, 2023)
The goal of this study is to examine how the Cognitive Apprenticeship Model and the Scaffolding Method are used in math instruction and to assess how well math instruction performs when the two approaches are used together. This research technique is library research, and the papers using the Cognitive Apprenticeship Model and the Scaffolding Method are the data sources. In order to determine whether the scaffolding method and the theory of the cognitive apprenticeship model are appropriate for use in the process of teaching mathematics, the data analysis approach employs the content analysis method. The results of the data analysis show that the cognitive apprenticeship model combined with the scaffolding method is not perceived to be better. This is because the scaffolding contained in the Cognitive Apprenticeship Model step is quite clear. Without having to use the scaffolding method, assistance can be provided in stages by using the sequencing components contained in the cognitive apprenticeship model.